2010
DOI: 10.1080/07448480903540531
|View full text |Cite
|
Sign up to set email alerts
|

No Fear, Just Relax and Play: Social Anxiety, Alcohol Expectancies, and Drinking Games Among College Students

Abstract: Findings suggest that social anxiety acts as a protective or a risk factor for DG participation among college students, depending upon AOE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
1
30
1
Order By: Relevance
“…Despite this theoretical basis, at present, only two studies have looked at the relationship of social anxiety with frequency of drinking game participation, and both failed to find a positive association (38,41). This finding may be due to the measurement of drinking game activity, with both studies asking participants how often they participate in drinking games.…”
Section: Social Anxiety and Drinking Game Participationmentioning
confidence: 59%
See 3 more Smart Citations
“…Despite this theoretical basis, at present, only two studies have looked at the relationship of social anxiety with frequency of drinking game participation, and both failed to find a positive association (38,41). This finding may be due to the measurement of drinking game activity, with both studies asking participants how often they participate in drinking games.…”
Section: Social Anxiety and Drinking Game Participationmentioning
confidence: 59%
“…While neither Johnson et al (38) nor Ham et al (41) found a positive relationship of social anxiety with frequency drinking game participation, they did find that the relationship was moderated by particular alcohol outcome expectancies (AOEs). AOEs are beliefs on projected consequences of drinking alcohol (42).…”
Section: Social Anxiety and Drinking Game Participationmentioning
confidence: 96%
See 2 more Smart Citations
“…Kenney et al (19) refines our understanding of the intersection between social anxiety and alcohol cognitions in respect to drinking games. Such research is important, as socially anxious students may avoid playing drinking games out of fear that they will embarrass themselves while playing (20) or may be more inclined to play drinking games since they facilitate rapid intoxication within a structured social context, thus alleviating anxiety (7,21). Drinking refusal self-efficacy and social anxiety may be especially important to consider as moderators of the association between drinking games participation and negative drinking consequences because socially anxious students may not be confident in their ability to refuse alcohol in the face of social pressure, thereby potentially increasing their risk for negative outcomes (19).…”
Section: Introductionmentioning
confidence: 99%